The effect of plant spacing on paddy yield / Daeng Dhariry Dahasry - Dahasry, Daeng Dhariry (Faculty of Plantation and Agrotechnology, 2018)
The Oryza sativa, commonly known as rice or paddy is one of the most commonly cultivated crops in the world. Paddy is cultivated for its edible seed in tropical to warm climates all over the world. It has turned into an essential nourishment for about half of the world human populace. This experiment was carried out at Mardi Tambun Tulang, Perlis to examine the effects of plant spacing on paddy yield. One rice cultivar, MARDI SIRAJ 297 were sown in three different plots of different plant spacing which are 15 x 15cm, 20 x 20cm, and 25 x 25cm. Wider spacing of 25 x 25cm has shown the best production in regard to all morphology and yield elements. It has brought the most astounding grain yield of 9 tons/ha. In contrast, the closer spacing of 20 x 20cm shown a slightly less performance regarding all investigated parameters and resulted in lower grain yield of 7 tons/ha. Additionally, spacing 15 x 15cm shown even lower performance of all parameters resulted in worst grain yield of 5 tons/ha. To conclude, the treatment with spacing of 25 x 25cm has proven to deliver the best performance for paddy cultivation.